(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A sports team is characterized by its unique identity, the placement of its members in different positions, a programme for action, and replacing or transferring of members from one position to another. The coach plays the managerial functions like planning, organizing, budgeting, scheduling, recruiting, public relations, leadership etc.Among these, leadership is the most significant because a leader is a person who motivates the team members and this action in turn contribute to the best performance and success. The coach and the team leader are two significant contributors to the performance effectiveness.In their 2002 book Primal Leadership, Daniel Goleman, Richard Boyatzis, and Annie McKee detailed their Six Emotional Leadership Styles theory.The theory highlights the strengths and weaknesses of six common styles – Visionary, Coaching, Affiliative, Democratic, Pacesetting, and Commanding. It also shows how each style can affect the emotions of your team members.The sport market comprises of distinct divisions like participatory sports, elite sports and the entertainment sports. These different divisions of the sport community are distinct in terms of their goals. Therefore, the kind of leadership expected from the coach and the team leader are distinct in nature. The leader must choose the design ideally tailored to the team’s requirements and to the individual circumstance.